Explore The Big Picture, forces shaping the future of humanity : shaping the future of humanity explore, imagine, act Part 1 - Van Rijn, Mario, ....-; van der Burg, René, ....- (Amsterdam : Pearson, 2021)
Are you interested in the state of our world? In the future of humanity? Have you ever wondered how the major decelopments of our time oure connected? Are you, in fact, interested in exploring the big picture?
Keywords: Humanity